2022
DOI: 10.3389/fimmu.2022.891175
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic signaling pathway-related long non-coding RNAs for predicting prognosis and immunotherapy response in breast cancer

Abstract: BackgroundThe clinical outcomes of breast cancer (BC) are unpredictable due to the high level of heterogeneity and complex immune status of the tumor microenvironment (TME). When set up, multiple long non-coding RNA (lncRNA) signatures tended to be employed to appraise the prognosis of BC. Nevertheless, predicting immunotherapy responses in BC is still essential. LncRNAs play pivotal roles in cancer development through diverse oncogenic signal pathways. Hence, we attempted to construct an oncogenic signal path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Concurrently, the LL group manifested a notably higher percentage of CDH1 mutations than its HH counterpart. An increased frequency of CDH1 mutations has been linked to a better prognosis, 89 reinforcing the veracity of our classification. Remarkably, within the HH subset of BRCA in Variant Classification, Shift code deletion mutations emerged as the second most prevalent, following Missense Mutations.…”
Section: Discussionsupporting
confidence: 55%
“…Concurrently, the LL group manifested a notably higher percentage of CDH1 mutations than its HH counterpart. An increased frequency of CDH1 mutations has been linked to a better prognosis, 89 reinforcing the veracity of our classification. Remarkably, within the HH subset of BRCA in Variant Classification, Shift code deletion mutations emerged as the second most prevalent, following Missense Mutations.…”
Section: Discussionsupporting
confidence: 55%
“…Emerging evidence has demonstrated that lncRNAs play an essential role in regulating immune cell infiltration, and some studies have also reported that methylation modification of lncRNAs regulates immune cell function in the tumor immune microenvironment [ 50 , 51 ]. In addition, we investigated the fundamental effects of the risk score on the regulation of immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the combined roles of diverse immune-related lncRNAs in models/signatures, which are prognostic predictors and markers of immune landscapes in BC, indicating their potential usefulness in clinical settings (139)(140)(141)(142)(143). Liu et al showed that a nomogram, based on seven immune-related lncRNAs, age, clinical stage, ER status, and BC subtype, is a predictor of OS in BC.…”
Section: Lncrna Prognostic Models/signaturesmentioning
confidence: 99%